Community Service of Farmers in Training on Making Liquid Organic Fertilizer in Wonosari Village, Gondangrejo District, Karanganyar Regency - Komariah Komariah; Eksa Rusdiyana; Dwi Priyo Ariyanto; Sumani Sumani; Bardhian Cahyo Aji Gumilang; Jaka Suyana; Hendricus William Siswantoro; Yoga Warana Tama; Saeful Bahri; Nifa Nurfiana; Fauzan Hariawan; Galuh Intan Kumalasari; Mufidah Anggi Wiyanti; Alfina Ayu S (Universitas Sebelas Maret, 2024)
Wonosari Village has quite a lot of rain-fed rice fields. The use of inorganic fertilizers in rice fields can also cause damage to soil structure, decreased fertility of soil microbes, environmental contamination, crop dependency, decline in biodiversity. Liquid organic fertilizer is a solution resulting from the decomposition of organic material originating from plant residues, agro-industrial waste, animal waste and human waste which contains more than one nutrient element. The aims of this service is to train farmers in making liquid organic fertilizer so that it can replace the use of inorganic fertilizers and be applied to their rice fields. The training program was held on February 25 2024 at Embung Munggur located in Wonosari Village, Gondangrejo District, Karanganyar Regency. The method of implementing this activity is carried out in several stages including introduction, implementation and evaluation. The results of the training showed that 80% of farmers who took part in the training understood how to make POC, and 60% wanted to make POC in the future. The post test results also show that community knowledge about LOF is 20% and skills are 60%. And It is hoped that it can continue to be developed so that farmers no longer depend on inorganic fertilizers.